PROBLEMS OF DAIRY INDUSTRY DEVELOPMENT IN THE COUNTRY’S ECONOMIC DEVELOPMENT - BONDARENKO, Valerii; LI, Zehao (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article analyzes the dairy industry in Ukraine, which is one of the leading components of the country’s food industry. The article examines the trends in the development of dairy processing enterprises, identifies the main challenges and opportunities for their further growth, and analyzes the global factors that influence the development of this industry and stimulate it to structural changes. Based on the research of domestic and foreign scholars, the article identifies the problems that impede the effective functioning of the dairy industry in Ukraine and determines which of them are the most critical in the current market conditions. The main problems are related to the low efficiency of dairy processing enterprises, the impact of global economic factors, the instability of the domestic market and the need to adapt to new political and environmental conditions. In particular, the crisis in the agricultural sector and the aggravation of force majeure caused by the military actions complicate the situation, requiring the industry to respond quickly and make structural changes. To meet these challenges, the dairy sector needs to implement the latest technologies, raise product quality standards and optimize business operations. In addition, unpredictable challenges, including the ongoing military action in the country, disrupt supply chains, increase production costs and threaten market share. The current situation in the dairy industry requires a comprehensive analysis to identify its strengths and weaknesses and to identify opportunities for growth. Particular attention is paid to market development prospects, investment opportunities, technological innovations in milk processing and raising product quality standards. The analysis shows that in order to remain competitive and increase efficiency, it is necessary to adapt to current trends and implement innovative solutions. The practical significance of the article is to provide recommendations for market participants to increase competitiveness and overcome current threats.